Controlled synthesis of EuPO4 nano/microstructures and core–shell SiO2@EuPO4 nanostructures with improved photoluminescence. Issue 82 (10th November 2017) - Yang, Kui-Suo; Wu, An-Ping; Zhao, Xin; Yan, Yu; Guo, Xue-Yuan; Bian, Yu-Long; Bao, Jin-Rong; Li, Wen-Xian; Zhu, Xiao-Wei
Abstract : EuPO4 nanoparticles coated on SiO2 submicro-spheres not only improve the photoluminescence properties but also change the symmetry of the Eu 3+ ions. Abstract : Cluster-like, flower-like and sphere-like EuPO4 nano/microstructures and uniform core–shell SiO2 @EuPO4 nanostructures have been controllably synthesized by the hydrothermal route and co-precipitation method, respectively. The as-synthesized products are characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and infrared spectroscopy (IR). The possible formation mechanism of the as-synthesized products is proposed. The photoluminescence properties demonstrate that the locations of the strongest peaks of nano/microstructured EuPO4 and core–shell nanostructured SiO2 @EuPO4 are different. In the emission spectrum of the core–shell SiO2 @EuPO4 nanostructures, the 5 D0 → 7 F2 transition is much stronger than the 5 D0 → 7 F1 transition, indicating that Eu 3+ ions occupy low symmetry sites in the EuPO4 lattice. Furthermore, the core–shell SiO2 @EuPO4 nanostructures have stronger emission intensity than the flower-like and sphere-like EuPO4 nano/microstructures.